Factors Affecting The Quality of Profit in Indonesia Banking Companies - Kurniawan, Ardik Rahmat; Khafid, Muhammad (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2016)
The aim of this research is to prove empirically the influence of Managerial Ownership, institutional ownership, profit growth, liquidity, and firm size on profit quality. Data that used to this research is secondary data and that data are taken from the official website of Indonesia Stock Exchange. The populations of this research are all of Banking Companies that list on Indonesia Stock Exchange (BEI) year 2012-2014 that numbered 42 companies. The samples that used to this research are 48 unit of analysis, with method of choosing the samples is purposive sampling technique. The analysis method used for this research is multiple linear regression analysis that analyzed with SPSS 21 program. The result shows that variable of institutional ownership and firm size influence on profit quality. Whereas managerial ownership, profit growth and liquidity does not affect to profit quality.